2016
DOI: 10.1097/htr.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Clinical Significance of Preinjury Recall Bias Following Mild Traumatic Brain Injury

Abstract: The recall bias was stronger and more likely clinically significant in MTBI patients with high postinjury symptoms. Multiple mechanisms appear to contribute to recall bias after MTBI, including the reattribution of preexisting symptoms to MTBI as well as processes that are not specific to MTBI (eg, related to compensation-seeking).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…included injured workers who received compensation benefits. Such a population might be more vulnerable to a true good-old-days bias (20) or might distort or misrepresent their pre-injury symptoms and functioning in relation to their compensation claim.…”
Section: Inconsistency Of Pre-injury Ratingsmentioning
confidence: 99%
See 3 more Smart Citations
“…included injured workers who received compensation benefits. Such a population might be more vulnerable to a true good-old-days bias (20) or might distort or misrepresent their pre-injury symptoms and functioning in relation to their compensation claim.…”
Section: Inconsistency Of Pre-injury Ratingsmentioning
confidence: 99%
“…Furthermore, some selfreport instruments (e.g., the Rivermead post-concussion questionnaire (RPQ) (19)) investigate a comparison of current symptoms with symptoms experienced before injury. The reliability and validity of pre-injury symptom ratings might be complicated because patients may not remember symptoms that occurred months earlier in an accurate manner (20). Moreover, following a negative event, patients may have the tendency to underestimate past problems and to view oneself as healthier in the past, which is referred to as the 'good-old-days' bias (21).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall bias of HRQL has been observed among patients with e.g. multiple sclerosis, psoriasis, cancer, injury and total hip arthroplasty [14][15][16][17] A study among patients with traumatic brain showed that recall bias was stronger in patients with high symptoms, which include memory problems [18]. This indicates that the size of recall bias may be higher among patients who experience memory problems compared to their counterparts.…”
Section: Introductionmentioning
confidence: 99%